ULTRA PETITA DECISIONS IN THE CONTEXT OF CRIMINAL LAW ENFORCEMENT IN INDONESIA - Ramiyanto Ramiyanto (Jurnal Hukum dan Peradilan, 2021)
The imposition of ultra petita decisions in the practice of criminal law enforcement in Indonesia continues to be going on today. This paper tries to examine the ultra petita decisions with the provisions in the Criminal Procedure Code, and the principle of freedom and the active role of judges. In answering the problem, the writer makes use of a type of normative legal research that’s done by researching positive law. The results of the discussion display that the Criminal Procedure Code doesn’t prohibit judges from imposing ultra petita decisions. In examining criminal cases, the judge can impose decisions that are outside of the requisition or exceed the requisition of the public prosecutor. The Criminal Procedure Code only stipulates that the basis for the judge in imposing a decision is the bill of indictment. Justification for the imposition of decisions is also based on the principle of judge freedomand judges are active. Under these two principles, judges are free to impose decisions without influence from other parties and actively searching for out facts that are revealed in court for the realization of material truth as the aims of criminal procedural law. The writer's recommendations are: 1) Criminal law enforcers (judges, public prosecutors, lawyers/ defendants) need to form a common awareness that ultra petita decisions are permitted; 2) The rule by which the judge gives the ultra petita decisions needs to be made immediately, each for the short and long term.